Island : Escape /. 3 - Korman, Gordon (Korman, Gordon. Island, 2001)
Six kids shipwrecked on an obscure Pacific island urgently need a plan to get home when they realize they are sharing their living space with a deadly group of smugglers--and the situation grows even more dire when the smugglers stumble across an atomic bomb left there in 1945.